Subsidizing Low Earnings: German Debates and U.S. Experiences - Waltraud Schelkle (Vierteljahrshefte zur Wirtschaftsforschung, 2000)
Promoting employment at low earnings figures prominently in several debates on how to make the German social welfare system more prone to job creation. In the U.S., about 15% of all civilian jobs are subsidized via the Earned Income Tax Credit, a transfer program that refunds income taxes beyond the amount actually paid. This article explores the lessons to be learnt from U.S. experiences with extensive earnings subsidization. Its potential role in the German system is rather different and more limited. However, earnings subsidies may be useful as a device to remove certain obstacles to labor force participation, which need not necessarily be on the supply side of the labor market but may also be found on the demand side. – – Die staatliche Förderung eines Niedriglohnsektors spielt in verschiedenen Debatten über den Zusammenhang von Arbeitslosigkeit und Sozialstaat in Deutschland eine Rolle. In den USA werden rund 15% aller zivilen Erwarbsarbeitsverhältnisse durch ein Steuerrückerstattungsprogramm, den sog. Earned Income Tax Credit, subventioniert. Dieser Beitrag untersucht die Lehren, die aus diesen US-amerikanischen Erfahrungen mit extensiver staatlicher Förderung der Niedriglohnbeschäftigung zu ziehen sind. Der Stellenwert solcher Einkommenssubventionen für Niedriglohnverdiener dürfte in Deutschland anders zu begründen und in der Reichweite begrenzter sein. Allerdings könnten Lohnsubventionen durchaus dazu dienen, bestimmte Hemmnisse der Erwerbsbeteiligung zu beseitigen, insbesondere auch solche, die ihr auf der Arbeitsnachfrageseite der Unternehmen entgegenstehen.
Keywords: 330; Lohnsubvention; Niedriglohn; Deutschland; USA